On‐Surface Synthesis and Characterization of Triply Fused Porphyrin–Graphene Nanoribbon Hybrids. (4th December 2019) - Mateo, Luis M.; Sun, Qiang; Liu, Shi‐Xia; Bergkamp, Jesse J.; Eimre, Kristjan; Pignedoli, Carlo A.; Ruffieux, Pascal; Decurtins, Silvio; Bottari, Giovanni; Fasel, Roman; Torres, Tomas
Abstract: On‐surface synthesis offers a versatile approach to prepare novel carbon‐based nanostructures that cannot be obtained by conventional solution chemistry. Graphene nanoribbons (GNRs) have potential for a variety of applications. A key issue for their application in molecular electronics is in the fine‐tuning of their electronic properties through structural modifications, such as heteroatom doping or the incorporation of non‐benzenoid rings. In this context, the covalent fusion of GNRs and porphyrins (Pors) is a highly appealing strategy. Herein we present the selective on‐surface synthesis of a Por–GNR hybrid, which consists of two Pors connected by a short GNR segment. The atomically precise structure of the Por–GNR hybrid has been characterized by bond‐resolved scanning tunneling microscopy (STM) and noncontact atomic force microscopy (nc‐AFM). The electronic properties have been investigated by scanning tunneling spectroscopy (STS), in combination with DFT calculations, which reveals a low electronic gap of 0.4 eV. Abstract : Auf ewig verbunden : Ein Porphyrin/Graphen‐Nanoband‐Hybrid wurde durch selektive Synthese auf einer Oberfläche hergestellt. Die atomar präzise Struktur des Hybrids wurde mittels bindungsauflösender Rastertunnelmikroskopie und Nicht‐Kontakt‐Rasterkraftmikroskopie charakterisiert. Rastertunnelspektroskopie und DFT‐Rechnungen zeigen, dass das System eine niedrige Bandlücke von 0.4 eV hat.